PATH-41. LONGITUDINAL MATCHED MUTATIONAL ANALYSIS IN RECURRENT AND MULTIFOCAL GLIOMAS - Daher, Ahmad (Neuro Oncol, 2019)
Re-resection of recurrent gliomas and multifocal gliomas are relatively uncommon resulting in limited understanding of the molecular profile of gliomas in those settings. Here we present a comprehensive mutational analysis via next generation sequencing (NGS) of 20 gliomas from 9 patients treated at our institution: one recurrent oligodendroglioma, one secondary glioblastoma (GBM), five locally recurrent primary GBMs, and two multifocal recurrent primary GBMs. Tumor mutational burden (TMB) range was 1.8–60.6 mutations/megabase (mt/Mb). Elevated TMB was seen in the initial (49.2 mt/Mb) and recurrent (60.6 mt/Mb) secondary GBM samples and in the distal recurrent GBM sample (50.9 mt/Mb) of one of the two patients with multifocal recurrent disease, suggesting a temozolomide-induced hypermutated state. Interestingly, the elevated TMB in the patient of multifocal recurrence occurred 5 years after completing 12 cycles of TMZ and was seen in the distal but not local focus of disease recurrence where TMB remained at 1.8 mt/Mb. The patient with multifocal (right frontal and right temporal) GBM at diagnosis developed recurrence in the temporal location only. NGS of the 2 resected tumors revealed 4 common somatic mutations, 3 mutations unique to the right frontal lesion and 8 mutations unique to the right temporal lesion. Additionally, our oligodendroglioma who was heavily treated in the six years prior to his last recurrence retained 4/6 of the initial somatic mutations and acquired 5 new ones upon the last recurrence. This analysis further highlights glioma spatiotemporal heterogeneity and the linear and divergent evolution upon disease recurrence and in the multifocal pre-treatment and recurrent settings. We also show that extensive oncogenic alterations can occur upon glioma recurrence, which is a major therapeutic barrier in managing recurrent disease, a barrier that can render the initial genomic profile of the disease, the basis of molecularly targeted therapy in the majority of cases, less meaningful.